Trimurti Leadership as Central Figure in Pondok Modern Darussalam Gontor - Ikhwan, Afiful; Marzuki, Kartini; Liswandi, Liswandi; Sabila, Ana Maulida (Letiges, 2023)
Indonesia is a pluralistic country because of its diversity of tribes, cultures, languages and customs, so it has various forms of Educational Institutions. Islamic boarding schools are the 'Father' of education in Indonesia and an indigenous institution born from Nusantara's local wisdom in a somewhat existential period. The characteristic of pesantren lies in its leadership in the hands of a Kiai. One of the pesantren that still exists today is Pondok Modern Darussalam Gontor (PMDG). So, this study aims to provide a discourse about the leadership of 'Trimurti' as the central figure in Pondok Modern Darussalam Gontor. The study is included in the library research. To facilitate data analysis, researchers used descriptive and content analysis techniques. Based on the results of the data analysis, the uniqueness of kiai's leadership lies in the charismatic character that creates a 'patron-client' pattern in the internal and external spheres. Trimurti of PMDG as a boarding school leader whose task is to educate the santri, applied two main methods: central figure (uswahhasanah) and formatting milieu or conducive environment. The whole life of the pesantren, both on a micro and macro scale, has been designed to transfer knowledge and value naturally in every daily activity.